2022
DOI: 10.3390/md20120735
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity by Oral Co-Exposure to Palytoxin and Okadaic Acid in Mice

Abstract: The frequent occurrence of marine dinoflagellates producing palytoxin (PLTX) or okadaic acid (OA) raises concern for the possible co-presence of these toxins in seafood, leading to additive or synergistic adverse effects in consumers. Thus, the acute oral toxicity of PLTX and OA association was evaluated in mice: groups of eight female CD-1 mice were administered by gavage with combined doses of PLTX (30, 90 or 270 μg/kg) and OA (370 μg/kg), or with each individual toxin, recording signs up to 24 h (five mice)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In another study, oral administration of low dose OA for 7 days did not alter serum AST and ALT levels or liver histology [40]. It was reported more recently that a single exposure to 370 µg/kg of OA slightly increased serum AST and ALT levels but did not induce alterations in the liver [41]. In other studies, OA concentrations in the liver were low, and no pathological changes were observed [23,42].…”
Section: Other Toxic Effects Of Repeated Oral Oa and Dtx-1 Administra...mentioning
confidence: 84%
“…In another study, oral administration of low dose OA for 7 days did not alter serum AST and ALT levels or liver histology [40]. It was reported more recently that a single exposure to 370 µg/kg of OA slightly increased serum AST and ALT levels but did not induce alterations in the liver [41]. In other studies, OA concentrations in the liver were low, and no pathological changes were observed [23,42].…”
Section: Other Toxic Effects Of Repeated Oral Oa and Dtx-1 Administra...mentioning
confidence: 84%
“…Dinoflagellates are generally notorious for their propensity to produce benthic harmful algal blooms (BHABs) containing marine biotoxins [2], which have a global impact on public health and aquatic ecological sustainability [3][4][5], thereby attracting the attention of the SCOR-IOC Global Ecology and Oceanography on Harmful Algal Blooms (GEO-HAB) program [6]. Lipophilic polyether phycotoxins from benthic dinoflagellates, such as palytoxin [7], ciguatoxins [8], and okadaic acid [9], may act as allelochemicals to help dinoflagellates gain a competitive advantage over benthic organisms [10,11], posing serious threats to human health when accumulated in seafood through the marine food chain [12,13].…”
Section: Introductionmentioning
confidence: 99%